Comparison of three stool antigen tests for Helicobacter pylori detection. Issue 10 (26th September 2003) - Andrews, J; Marsden, B; Brown, D; Wong, V S; Wood, E; Kelsey, M
Abstract : Background: Active Helicobacter pylori infection can be diagnosed by invasive (biopsy based) or non-invasive methods, such as stool antigen testing. Aims: To compare three stool antigen enzyme immunoassay kits—Premier Platinum Hp SA, FemtoLab Cnx, and Hp Ag—with biopsy based methods for the detection of H pylori in previously undiagnosed patients. Methods: One hundred and eleven adults with dyspepsia referred for endoscopy provided a stool sample for testing and had biopsies taken. Patients were considered H pylori positive if two out of three invasive tests were positive or if culture alone was positive. Results: The sensitivities and specificities of the Premier Platinum Hp SA, FemtoLab Cnx, and Hp Ag stool antigen kits when compared with biopsy based diagnosis were, 63.6%, 88.0%, and 56.0% and 92.6%, 97.6%, and 97.6%, respectively. Conclusions: FemtoLab Cnx may be considered as an alternative to urea breath testing in the initial diagnosis of patients with dyspepsia who do not require immediate endoscopy. Stool testing has the potential advantages of being simple to perform, relatively cheap, and samples can be submitted directly from primary care.